A Theoretical Analysis of Pore Size Distribution Effects on Shale Apparent Permeability. (26th November 2017) - Tian, Shouceng; Ren, Wenxi; Li, Gensheng; Yang, Ruiyue; Wang, Tianyu
Abstract : Apparent permeability is an important input parameter in the simulation of shale gas production. Most apparent permeability models assume a single pore size. In this study, we develop a theoretical model for quantifying the effect of pore size distribution on shale apparent permeability. The model accounts for the nonuniform distribution of pore sizes, the rarefaction effect, and gas characteristics. The model is validated against available experimental data. Theoretical calculations show that the larger the pore radius, the larger the apparent permeability. Moreover, the apparent permeability increases with an increase in the width of pore size distribution, with this effect being much more pronounced at low pressure than at high pressure.